Desenvolvimento de corpos porosos de ZnO para fotodegradação de fluoxetina - Duran, Karla De Almeida (2024)
Concerns about the environment have been a topic of high attention due to the persistent nature of emerging organic contaminants (EOC), such as dyes and pharmaceuticals in water bodies. EOC’s of pharmaceutical origin have expanded considerably, given the expansion of the population and variants and the stress of everyday life in addition to the discovery of new drugs, showing an increase in medication consumption. Regarding the disposal and human excretion routes of these medicines, many of them persist in water systems, even after treatment, generating an environmental liability that is harmful to living beings. Due to this context of emerging pollutants in wastewater, much study has been done to understand the main effects and ways to mitigate them. In terms of the consumption of antidepressant medications, fluoxetine is one of the main drugs prescribed and given its permanent nature in the environment under visible light, it is relevant to explore routes to eliminate FLX in order to minimize the impact on the ecosystem. This research investigated the photodegradation of fluoxetine using zinc oxide (ZnO), in the form of porous pieces, in order to identify a method that allows reducing the negative impact caused to living beings when in contact with these contaminants in water. These porous ZnO parts were obtained through the replica processing route, which processes the formulation and preparation of several slips until the selection of the most stable, conventional one suitable for the selected manufacturing process. The porous ceramic material obtained after sintering was immersed in a fluoxetine (FLX) solution under UV-Vis radiation and the solution was investigated by means of Liquid Column Chromatography in order to analyze the reduction of the quantity of fluoxetine present in the environment, through photodegradation. The presence of ZnO in the FLX solution accelerated the drug removal rate by around 20-30%, starting from a concentration of 10 mg/L in solution, in the first 15 min. of exposure when compared to photolysis. The reuse of the ceramic bodies, and the rate of formation of by-products of the fluoxetine compound is invariable, indicating that ZnO does not cause an increase or reduction of these compounds.